Monitoring status and trends in genetic diversity for the Convention on Biological Diversity: An ongoing assessment of genetic indicators in nine countries - Sean Hoban; Jessica M. da Silva; Alicia Mastretta‐Yanes; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Joachim Mergeay; Ivan Paz‐Vinas; Keiichi Fukaya; Fumiko Ishihama; Rebecca Jordan; Viktoria Köppä; et al. (Conservation Letters, 2023)
Abstract Recent scientific evidence shows that genetic diversity must be maintained, managed, and monitored to protect biodiversity and nature's contributions to people. Three genetic diversity indicators, two of which do not require DNA‐based assessment, have been proposed for reporting to the Convention on Biological Diversity and other conservation and policy initiatives. These indicators allow an approximation of the status and trends of genetic diversity to inform policy, using existing demographic and geographic information. Application of these indicators has been initiated and here we describe ongoing efforts in calculating these indicators with examples. We specifically describe a project underway to apply these indicators in nine countries, provide example calculations, address concerns of policy makers and implementation challenges, and describe a roadmap for further development and deployment, incorporating feedback from the broader community. We also present guidance documents and data collection tools for calculating indicators. We demonstrate that Parties can successfully and cost‐effectively report these genetic diversity indicators with existing biodiversity observation data, and, in doing so, better conserve the Earth's biodiversity.